Nilai Filosofis, Etika Dan Ritual Bangunan Bale Dangin Sakenem - Arya Bagus Mahadwijati Wijaatmaja; I Gusti Agung Laksmi Swaryputri (Universitas Dwijendra, 2020)
Traditional Balinese architecture is a regional architecture that needs to be preserved in this globalization era. The knowledge and implementation of Balinese architecture is also increasingly diminished as the modernity influences the building (architecture). This is followed by the presence of a present-day architectural style dominated by minimalist architecture. The application of Balinese architecture today can only be found in the application of ornaments in the building façade. There are several types of traditional Balinese buildings that still survive until now such as Bale Dangin, Bale Meten/sakutus, Bale Dauh, Jineng/Kelumpu, Paon and others, the building is still surviving in terms of shape, function, and materials used since the first time. Bale Dangin serves as a place of ceremonies, so it is vital to the life of Balinese people who practice Hinduism. Therefore, it is necessary to do the effort to preserve and keep the cultural values of Bale Dangin. The research on Bale Dangin was conducted based on the lack of references that discussed the Bale Dangin thoroughly. This research also aims to determine the peculiarities of the building of Bale Dangin Sakenem seen from philosophical value, ethics and ritual, and get a form of guidelines regarding the building of Bale Dangin Sakenem which can be used as reference in designing or constructing the Bale Dangin Sakenem building. The research approach used in this research is based on qualitative descriptive research methods. Qualitative research intends to understand the phenomenon of what is experienced by research subjects such as behavior, perception, motivation, action, holistically and with descriptions in the form of words and language in a particular context that Nature and by utilizing a variety of natural methods. The method of descriptive qualitative research on this study was used to describe the facts in the field related to the condition of Bale Bale Dangin Sakenem in the case study used, judging by the function of building, form, layout, as well as Development process from the beginning until the building is ready to be occupied. This research is expected to produce a special reference to the Bale building of the sakenem in a traditional Balinese house seen from the philosophical value, ethics and ritual and construction process. Indirectly, this can also preserve Balinese architecture that is in accordance with philosophy and meaning